TABLE TENNIS AS A MEANS OF DEVELOPING APPLIED ABILITIES AND INCREASING MOTOR ACTIVITY (Physical Culture and Sport: Scientific Perspective, 2025)
In today's unstable world, where most pupils, students and adults spend a significant part of their time in a sitting or other non-motor position - at home, at school, at work, in transport, at leisure - the issue of maintaining and accumulating a sufficient level of motor activity becomes extremely urgent. Improving the indicators of the development of applied abilities for successful everyday and professional activities is also relevant. A sedentary and sedentary lifestyle is one of the key risk factors for the development of cardiovascular and respiratory diseases, obesity, diabetes, musculoskeletal disorders and psycho-emotional exhaustion.In this regard, the search for such types of physical activity and sports activities that combine accessibility, safety, a versatile effect on the body and at the same time have an applied, playful and motivational nature is of particular importance. One of these types is a sports game, table tennis - a dynamic, but low-traumatic sport that helps improve coordination of movements, develop reaction speed, spatial thinking, concentration of attention and general endurance. Due to the small spatial and financial support, table tennis is available in secondary education institutions, higher education, children's and youth sports schools, sports and multi-sports clubs and even at home. This type of physical activity is recommended for people of all ages, in particular children, schoolchildren and students, middle-aged and elderly people, as an effective means of preventing hypodynamia and maintaining a high quality of life.Thus, the study of table tennis as a means of developing applied abilities and increasing motor activity is extremely relevant and promising in the context of popularizing a healthy, active and safe lifestyle, physical education and general health improvement of the population of Ukraine.
Keywords: table tennis; physical activity; secondary education institutions; higher education institutions; children's and youth sports schools; sports and multi-sports clubs; development of applied abilities; healthy; active and safe lifestyle; motor activity; psychophysiological state; active leisure; prevention of hypodynamia